A proposal and simulation analysis for a novel architecture of gate-all-around polycrystalline silicon nanowire field effect transistor - El-amiri, Asseya; Demami, Fouad (International Journal of Electrical and Computer Engineering (IJECE), 2024)
A proposal for a novel gate-all-around (GAA) polycrystalline silicon nanowire (poly-SiNW) field effect transistor (FET) is presented and discussed in this paper. The device architecture is based on the realization of poly-SiNW in a V-shaped cavity obtained by tetra methyl ammonium hydroxide (TMAH) etch of monocrystalline silicon (100). The device’s behavior is simulated using Silvaco commercial software, including the density of states (DOS) model described by the double exponential distribution of acceptor trap density within the gap. The electric field, potential, and free electron concentration are analyzed in different nanowire regions to investigate the device's performance. The results show good performance despite the high density of deep states in poly-SiNW. This can be explained by the strong electric field caused by the corner effect in the nanowire, which favors the ionization of the acceptor traps and increases the free electron concentration.